2017
DOI: 10.1093/ejcts/ezx105
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative air leak measured after lobectomy is associated with postoperative duration of air leak

Abstract: The air leak measurement using the ventilator parameters after lung resection may assist in estimating the risk of postoperative prolonged air leak. An IAL > 500 ml/min may warrant the use of intraoperative preventative measures, particularly after video-assisted thoracic surgery lobectomy where a submersion test is often unreliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Lastly, we found that initial air leaks were associated with both complication and reintervention rates. Therefore, careful dissection, early awareness of air leaks, and prevention strategies to decrease air leaks by all means, e.g., sealant use, in the operating room are important intraoperative factors that can reduce air leak-related complications [22].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we found that initial air leaks were associated with both complication and reintervention rates. Therefore, careful dissection, early awareness of air leaks, and prevention strategies to decrease air leaks by all means, e.g., sealant use, in the operating room are important intraoperative factors that can reduce air leak-related complications [22].…”
Section: Discussionmentioning
confidence: 99%
“…4 The greater the degree of intraoperative air leak, the higher the risk of developing postoperative prolonged air leak. 3 Intraoperative air leak can be of bronchial or alveolar origin. 1 Bronchial leak should be controlled surgically with either sutures or staples.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies have shown that patients with more intraoperative air leaks are at higher risk of developing prolonged postoperative air leak. 3 Intraoperative air leaks can be measured collectively by ventilator parameters (the difference between inspiratory and expiratory tidal volume), 3 or by the normal saline test that identifies the leakage points and the degree of leakage at each point. 10 Traditional methods (suturing and stapling) can be used to control intraoperative air leak, but with an alveolar air leak, these methods may cause more tears in the lung parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…The second way could be the adoption of a meticulous surgical technique as appropriate tissue manipulation and retraction, mobilization of all intrapleural adhesions, division of the inferior pulmonary ligament, routine pre-compression of staple lines, fissureless/fissurelast technique, and select use of surgical sealant (9,10). Finally, an objective intraoperative measurement of intraoperative air leak (IAL) is of importance (11,12).…”
Section: Introductionmentioning
confidence: 99%